Structural and Photoluminescence Properties of Ca2+-Substituted Self-Activated Photoluminescence Material of Na2TiSiO5 - Dzaky Dian Ruhimat; Fainan Failamani; Bambang Prijamboedi (Journal of Mathematical and Fundamental Sciences, 2023)
The effects of Ca2+ substitution on the structural and optical properties of Na2TiSiO5 were studied. It was expected that the Ca2+ ions would replace Na+ ions and change the coordination of Ti4+-O2- as a luminescence center. Na2(1‑x)CaxTiSiO5 (x = 0.00, 0.50, 1.00) samples were synthesized using the solid-state method, and their structural properties, the local Ti4+-O2- coordination, the absorption spectra, and the photoluminescence properties were studied. The electronic structure of Na2(1-x)CaxTiSiO5 with x = 0.00 and 1.00 was also calculated using the Full Potential Linear Augmented Plane Wave (FP-LAPW) method to explain some of the observed properties. The Ca2+ substitution resulted in a phase transformation from an orthorhombic to a monoclinic structure. The number of TiO6 octahedra increased with the increase of Ca2+ and correlated with the decrease of PL emission intensity of the Na2(1‑x)CaxTiSiO5 samples. The Ti-3d bands in the CaTiSiO5 were more dispersive than in the Na2TiSiO5 and were responsible for the PL emission intensity reduction.